(untitled) (Altre Modernità, 2016)
This article aims to recognize and describe some of the characteristics of the student movement of 2006 in Chile known as the "Penguin Revolution". It’s a contribution to the expansion of the public debate about the results of the country’s education policy implemented since the return of democracy in 1990. Therefore, it analyzes and proposes different interpretations of the new form of participation and advocacy of high school students and their ability to influence the political agenda of the country. The proposed methodology is to reflect and respond to these questions through a documentary work taking into consideration the comparison between the educational policies in Chile and the international efforts in the struggle for the right to education. Also, it introduces an approach to the young people of that time, their training as students, self-proclaimed as "sons of democracy" as it was raised during the first post-dictatorship governments. The focus of this study, which looks at the youth from a different perspective, goes beyond the subjectivity and building of a common identity. The impact on the political and social life is undeniable, their main role broke the inertia of the first generation in transition period after ’90